Migratory functionalization of unactivated alkyl bromides for construction of all-carbon quaternary centers via transposed tert-C-radicals - Chuan Zhu (Nature Portfolio, 2020)
Formation of tertiary C(sp3)-C bonds is a formidable challenge due to steric interactions and low barriers for isomerization of intermediates. Here, the authors show a Ni-catalyzed migratory 3,3-difluoroallylation of unactivated alkyl bromides at remote tertiary carbon centers.